IMPLANTAÇÃO DE TELEMETRIA VEICULAR PARA GESTÃO NO REGISTRO E CONTROLE DE JORNADA DE TRABALHO DE MOTORISTAS PROFISSIONAIS - NAZARÉ, JUCILENE (2022)
Innovation has become essential for companies seeking economic efficiency, improvements in organizational development, and for those seeking to prevent future problems. Following this premise, this work was developed, where to solve a problem, the company decided to innovate. The problem situation found was the lack of management and the erroneous filling of information in the logbook, which was done manually, contributing to the burdening of labor processes. Thus, in order to make an innovative intervention, it was defined as a technical objective to implement the vehicular telemetry system to assist in the registration and control of the working hours of the drivers' employees, using as scientific technical basis the Law 13.103/2015 and the dynamic capabilities, focusing on innovation capacity and absorption capacity. To develop this work, data were collected through documentary research, non-participant observations and non-structured interviews. For data analysis, document analysis and content analysis were used. Action plans were also developed, using the 5W2H model. A total of 632 logbooks were analyzed between the period January/2021 to August/2021, where it was found that 14.08 % were filled out correctly, 30.70% were not filled out, and 55.22% were filled out incorrectly. The main filling error was the lack of closure of the working day, found in 83.67% of the analyzed logbooks. In second place was the lack of filling in the mandatory stops, with 55.30%. In third place, with 40.97%, was the error of not marking the start and/or end time of the mandatory stops. It was also verified that in the year 2021 the company suffered 11 labor lawsuits with claims over R$ 100,000.00, totaling R$ 4,987,737.82. It was also identified during the interviews that the company was aware of the problem, and knew the importance of the logbook as the main evidence in labor lawsuits, but had difficulties in managing these documents and making their employees follow the norms and procedures. After these surveys, it became evident that the system used by the company was outdated, urgently needing to implement an efficient and practical control system that would provide the necessary support so that the company would not continue suffering lawsuits of this magnitude. Law 13,103/2015 informs that the working hours must be filled in by the employee through systems made available by the employer. Thus, complying with the legislation and with the technical objective of this work, a system called vehicular telemetry was implemented, which operates through a tablet installed in the trucks, where the filling out is done digitally by the employee through login and password, and the information is sent in real time to the company, allowing it to know immediately the actions taken. Besides this system, a manual of rules and procedures was also developed to present in writing what the company requires from its driver employees, making them aware of their duties. In short, with this work, it was possible to innovate in the management of this company, showing that it has the capacity for innovation and absorption. And thus, finally implement a system that allows the company to efficiently manage the registration and control of the drivers' working hours, contributing to not burdening future labor lawsuits.